2016
DOI: 10.1088/0957-0233/27/7/075601
|View full text |Cite
|
Sign up to set email alerts
|

An improved torsion pendulum based on image processing for single fibers

Abstract: An improved torsion pendulum technique based on image processing is developed, which allows the measurement of the torsional oscillation of individual fibers. The torsion pendulum is composed of a length of fiber specimen and a ring-shaped mass attached to one of its ends. The oscillation motion of the mass is recorded with a video camera overhead. An image processing method is developed to accurately calculate the twist angle of single fibers in the torsion pendulum. All images are firstly converted into matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 47 publications
5
16
0
1
Order By: Relevance
“…Such a calibration method has been proved to be unsatisfactory because of the friction in the pulley used to redirect the load. Here, we adopt an improved torsion pendulum based on image processing [27] to determine the shear modulus of the torsion wire accurately, as shown in Fig.2(a). Here, we chose tungsten wires ranging in diameter from 15 to 40μm as the torsion wires.…”
Section: Calibration Of the Torsion Wirementioning
confidence: 99%
See 2 more Smart Citations
“…Such a calibration method has been proved to be unsatisfactory because of the friction in the pulley used to redirect the load. Here, we adopt an improved torsion pendulum based on image processing [27] to determine the shear modulus of the torsion wire accurately, as shown in Fig.2(a). Here, we chose tungsten wires ranging in diameter from 15 to 40μm as the torsion wires.…”
Section: Calibration Of the Torsion Wirementioning
confidence: 99%
“…The oscillation frequency was then determined by the Fast Fourier Transform (FFT). The shear modulus of the tungsten wire can be calculated as [26,27]   . The detailed description of the torsion pendulum is given by Yu et al [27] As shown in Fig.…”
Section: Calibration Of the Torsion Wirementioning
confidence: 99%
See 1 more Smart Citation
“…Today the torsion balance or pendulum is still one of the most sensitive tools for measuring the torsional properties of individual fibers 14,15,21,22 . In this study we use an improved torsion pendulum based on image processing 22 (see Fig.1 (a)) to explore the torsional relaxation dynamics of the dragline silks from two orb-weaver species: Nephila edulis (N. edulis) and Nephila pilipes (N. pilipes) spiders, and other types of fibers (e.g. metallic wires, carbon fiber, and human hair).…”
mentioning
confidence: 99%
“…1(c), panel III and IV). The bob was taken to initial twist angles corresponding to ~0.61×10 -3 and~1.22×10 -3 in strain, When the initial surface strain is within the elastic region (<0.6×10 -3 ) 22 , the pendulum oscillates around its original position, see panel III of fibers (e.g. human hair), and metallic wires (e.g.…”
mentioning
confidence: 99%